A single-palladium atom modified porous boron nitride nanomaterial, a preparation method and application thereof
By preparing porous boron nitride nanomaterials modified with single palladium atoms as catalysts, the problems of large palladium catalyst consumption and difficult recovery in the Suzuki coupling reaction were solved, achieving efficient, stable, and environmentally friendly catalytic effects, which are suitable for large-scale production.
Patent Information
- Application Number
- CN202311166739.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-12-26
- Estimated Expiration
- 2043-09-11
AI Technical Summary
The existing Suzuki coupling reaction uses large amounts of palladium catalyst, is costly and difficult to recycle, impacts the environment, and has insufficient catalyst stability and selectivity.
Porous boron nitride nanomaterials modified with single palladium atoms were used as catalysts. Porous boron nitride precursors were prepared by melamine and boric acid and reacted with Pd(OAc)2 to form porous boron nitride nanomaterials with single palladium atoms uniformly dispersed on the surface and inside, which were then used for Suzuki coupling reactions.
It achieves high activity and high selectivity catalysis with low precious metal loading. The catalyst is easy to separate and recover from the reaction system. The reaction conditions are mild and environmentally friendly, making it suitable for large-scale production.
Smart Images

Figure CN117244578B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of nanomaterial preparation, and particularly relates to a single-palladium-atom-modified porous boron nitride nanomaterial and a preparation method and application thereof. BACKGROUND
[0002] Suzuki coupling reaction is one of the most widely used chemical reactions in the synthesis of organic chemistry. The classic Suzuki reaction uses aryl boronic acid and aryl halide as reaction substrates, and under the action of a palladium catalyst, a C-C coupling product is rapidly generated. Although the classic Suzuki coupling reaction has the advantages of good substrate adaptability, high efficiency and wide application, in recent years, chemists have still been trying to optimize the Suzuki coupling reaction, mainly including reducing the amount of palladium catalyst and phosphine ligand, reacting in aqueous solution, and developing recyclable catalysts, in an attempt to reduce the raw material cost and environmental hazards of the Suzuki coupling reaction. Under this background, the development of a nano-catalyst suitable for the Suzuki coupling reaction has become a research hotspot in this field. SUMMARY
[0003] The application aims to provide a single-palladium-atom-modified porous boron nitride nanomaterial and a preparation method thereof, and the prepared catalyst is used for Suzuki coupling reaction.
[0004] To achieve the above-mentioned purpose, the technical scheme adopted by the application is as follows:
[0005] A preparation method of a single-palladium-atom-modified porous boron nitride nanomaterial, in which melamine and boric acid are used as raw materials to prepare a porous boron nitride precursor, and the precursor is reacted with Pd(OAc)2 to obtain a porous boron nitride nanomaterial with a large specific surface area and pores, which is modified by a single palladium atom on the surface and inside.
[0006] Specifically, the method comprises the following steps:
[0007] 1) Melamine and boric acid are mixed, and the pH of the system is adjusted to 8-9; a sol-gel is prepared by stirring at 40-80 DEG C in a constant-temperature water bath for 24 hours;
[0008] 2) The gel obtained in step 1) is pre-frozen at minus 60-65 DEG C for 3 hours, and the pre-frozen gel is freeze-dried to obtain a white fibrous solid;
[0009] 3) The white fibrous solid obtained in step 2) is calcined at 450-500 DEG C for 2-4 hours under the protection of N2 atmosphere, and cooled to room temperature to obtain a porous boron nitride precursor;
[0010] 4) The porous boron nitride precursor obtained in step 3) is placed in an acetone solution and stirred, and Pd(OAc)2 is added at 0°C and the reaction is continued to be stirred for 3h, a filter cake is obtained by suction filtration, and a light yellow solid is obtained by drying under an infrared lamp;
[0011] 5) The light yellow solid obtained in step 4) is calcined at 600-1100°C for 2h under N2 atmosphere, and the obtained gray-black solid is washed with water and alcohol, dried under an infrared lamp, and a single-palladium atom modified porous boron nitride nanomaterial is obtained.
[0012] The material is a single-palladium atom modified porous boron nitride nanomaterial dried under an infrared lamp, and the particle size is 5-400nm, and the drying temperature is 70-100°C.
[0013] The molar ratio of the melamine and the boric acid is 1:2-3, and when the dosage of the melamine is 10mmol, the dosage of the Pd(OAc)2 is 0.5-2mmol.
[0014] The single-palladium atom modified porous boron nitride nanomaterial prepared by the method has a particle size of 5-400nm, and the metal palladium is dispersed in a single atom form on the surface and inside of the porous boron nitride nanomaterial.
[0015] The loading amount of the active metal palladium is 0.1-5% of the total mass of the material.
[0016] The single-palladium atom modified porous boron nitride nanomaterial is used as a catalyst for a Suzuki coupling reaction.
[0017] The Suzuki coupling reaction is a reaction of an organoboron compound and an organic halogen compound under the catalysis of the material, at room temperature, under normal pressure and air atmosphere, and the reaction solvent is water and a non-toxic organic solvent; wherein when the halide in the reaction substrate is 1mmol, the dosage of the catalyst is 0.01-0.05g.
[0018] The single-palladium atom modified porous boron nitride nanomaterial has not only the excellent properties of the original boron nitride nanomaterial, but also the dispersion and linkage of the palladium metal nanoparticles on the boron nitride, and the charge transfer between the boron nitride and the palladium metal, which all have a positive influence on the catalytic performance; and the single-palladium atom modified porous boron nitride nanomaterial is easy to be separated from the reaction system by a conventional method, so that it not only has a good catalytic effect, but also is easy to be separated from the reaction product after the completion of the catalytic reaction. Meanwhile, in the Suzuki coupling reaction experiment, it is confirmed that the prepared catalyst indeed has a good catalytic effect and stability, and is easy to be separated and repeatedly used.
[0019] Compared with the prior art, the present application has the following beneficial effects:
[0020] The single-palladium atom modified porous boron nitride nanomaterial has a simple preparation method, is easy to operate, and is suitable for large-scale production.
[0021] The single-palladium atom modified porous boron nitride nanocatalyst has the characteristics of low noble metal loading, high metal atom utilization rate, and metal particles not easy to agglomerate, can effectively catalyze the occurrence of the Suzuki coupling reaction under relatively mild conditions, and has the advantages of high activity, high selectivity, stable catalyst, and easy recovery.
[0022] In addition, the reaction process is environmentally friendly, and the technical and economic effects are remarkable, which is conducive to popularization. BRIEF DESCRIPTION OF DRAWINGS
[0023] Figure 1 XRD patterns of Pd-BNPs-1100 and original BNPs-1100 prepared in Example 1 of the present application.
[0024] Figure 2 SEM images of Pd-BNPs-1100 prepared in Example 1 of the present application; wherein, A is a partial SEM image taken at a working distance of 8.3 mm and a magnification of 3000, and B is an SEM image taken at another position at a working distance of 8.3 mm and a magnification of 3000.
[0025] Figure 3 TEM images of Pd-BNPs-1100 prepared in Example 1 of the present application; wherein, A is a TEM image taken at a scale of 500 nm, and B is a TEM image taken at a scale of 200 nm.
[0026] Figure 4 XPS images of Pd-BNPs-1100 prepared in Example 1 of the present application; wherein, A is the full scan XPS spectrum of Pd-BNPs-1100, B is the high-resolution C three-dimensional spectrum, C is the high-resolution B three-dimensional spectrum, and D is the high-resolution Pd three-dimensional spectrum.
[0027] Figure 5 Catalytic performance and cycle performance test chart of Pd-BNPs-1100 prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0028] The present application will be described in detail below through specific examples, but these examples do not constitute limitations on the content of the present application. At the same time, the examples only give part of the conditions to achieve the purpose, but do not mean that these conditions must be met to achieve this purpose.
[0029] The single-palladium atom modified porous boron nitride nanomaterial obtained in the present application contains palladium base with high catalytic ability, and has the characteristics of large specific surface area and porous. The palladium loaded on the single-palladium atom modified porous boron nitride nanomaterial has the characteristics of small particle size and uniform dispersion, and thus has excellent catalytic effect. Moreover, the single-palladium atom modified porous boron nitride nanomaterial also has good structural stability, and is easy to separate from organic medium, and can be used as a catalyst for Suzuki coupling reaction.
[0030] Example 1:
[0031] The single-palladium atom modified porous boron nitride nanomaterial is prepared according to the following specific steps.
[0032] 1) 1.575 g of melamine and 1.545 g of boric acid are weighed and uniformly mixed, and then 100 ml of deionized water is added to prepare a sol gel. A calcium hydroxide solution and an ammonia water solution are slowly added dropwise to adjust the pH to 8-9, and then the mixture is subjected to constant temperature of 40℃ under magnetic stirring for 24 h to obtain a milky white gel;
[0033] 2) The gel obtained in step 1) is pre-frozen at -60-65℃ for 3 h, and then the pre-frozen gel is freeze-dried to obtain a white fibrous solid;
[0034] 3) The white fibrous solid obtained in step 2) is placed in a corundum boat and placed in the middle of a tube furnace, and then calcined at 450℃ for 2 h under N2 atmosphere protection, and then cooled to room temperature to obtain a porous boron nitride precursor;
[0035] 4) The porous boron nitride precursor obtained in step 3) is placed in an acetone solution and stirred, and then 0.112 g of Pd(OAc)2 is added at 0℃, and then the mixture is continuously stirred for 3 h of reaction, and then the filter cake is obtained by suction filtration, and then the filter cake is dried by infrared lamp to obtain a light yellow solid;
[0036] 5) The light yellow solid obtained in step 4) is placed in a corundum boat and placed in the middle of a tube furnace, and then calcined at 1100℃ for 2 h under N2 atmosphere protection, and then cooled to room temperature, and then the obtained gray-black solid is washed with water and alcohol, and then dried by infrared lamp, and then the single-palladium atom modified porous boron nitride nanomaterial is obtained after drying, which is recorded as Pd-BNPs-1100 (see Figures 1-4 ).
[0037] Meanwhile, the porous boron nitride precursor (gray-black solid) obtained in step 3) is washed with water and alcohol, and then dried by infrared lamp, and then the single-palladium atom modified porous boron nitride nanomaterial is obtained after drying, which is recorded as BNPs-1100 (see Figure 1 ).
[0038] The structure information and crystal phase of Pd-BNPs-1100 and original BNPs-1100 are analyzed by XRD, as shown in Figure 1As shown, both Pd-BNPs-1100 and the original BNPs-1100 exhibited distinct characteristic peaks at 2θ = 26.7°, corresponding to the (002) lattice plane of the typical hexagonal boron nitride structure (JCPDS No. 1), indicating that the crystal structure of boron nitride was not destroyed by the reaction. In the XRD pattern of Pd-BNPs-1100, clear new diffraction peaks appeared at 2θ = 40.1°, 46.6°, and 68.1°, belonging to the (111), (200), and (220) lattice planes of palladium, respectively. Figure 2 The SEM images show that Pd-BNPs-1100 is a rod-shaped or strip-shaped material. Figure 3 TEM images show that palladium is uniformly dispersed on the surface and inside the Pd-BNPs-1100 material. XPS was used to investigate the electronic information and existence states of palladium in Pd-BNPs-1100. Figure 4 The existing survey scan XPS spectrum (A) shows five sharp binding energy peaks in Pd-BNPs-1100, belonging to B, C, Pd, N, and O, respectively; and the high-resolution three-dimensional spectrum of C (B) shows binding energy peaks at 284.80 eV, 286.52 eV, and 287.07 eV corresponding to C=C, CO, and C=O functional bonds, respectively; in addition, the high-resolution three-dimensional spectrum of B (C) shows binding energy peaks at 190.83 eV and 192.16 eV corresponding to BN and BO functional bonds, respectively; and the high-resolution three-dimensional spectrum of Pd shows two binding energy peaks (D), with two spin-orbit dual states belonging to Pd 3d 5 / 2 and Pd 3d 3 / 2 The binding energy peaks at 336.05 eV and 341.27 eV correspond to Pd(0)NPs.
[0039] Example 2:
[0040] 1) Weigh 1.575g of melamine and 1.545g of boric acid and mix them evenly. Add 100ml of deionized water to prepare a sol-gel. Slowly add calcium hydroxide solution and ammonia solution to adjust the pH to 8-9. Keep the temperature at 40℃ for 24h under magnetic stirring to obtain a milky white gel.
[0041] 2) Pre-freeze the gel obtained in step 1) at -60 to -65°C for 3 hours, and freeze-dry the pre-frozen gel to obtain a white fibrous solid;
[0042] 3) The white fibrous solid obtained in step 2) was placed in a corundum boat, placed in the middle of a tube furnace, and calcined at 450°C for 2 hours under N2 atmosphere protection. After cooling to room temperature, a porous boron nitride precursor was obtained.
[0043] 4) The porous boron nitride precursor obtained in step 3) was placed in an acetone solution and stirred, 0.112 g of Pd(OAc)2 was added at 0°C and the reaction was continued to stir for 3 h, the filter cake was obtained by suction filtration, and a light yellow solid was obtained by drying under an infrared lamp;
[0044] 5) The light yellow solid obtained in step 4) was placed in a corundum boat and placed in the middle of a tube furnace, calcined at 1000°C for 2 h under N2 atmosphere, cooled to room temperature, and the obtained gray-black solid was washed with water and alcohol, dried under an infrared lamp, and a single palladium atom modified porous boron nitride nanomaterial was obtained after drying, denoted as Pd-BNPs-1000.
[0045] Example 3:
[0046] 1) 1.575 g of melamine and 1.545 g of boric acid were weighed and mixed uniformly, and then 100 ml of deionized water was added to prepare a sol-gel, a calcium hydroxide solution and an ammonia solution were slowly added to adjust the pH to 8-9, and a white gel was obtained under magnetic stirring at 40°C for 24 h;
[0047] 2) The gel obtained in step 1) was pre-frozen at -60 to -65°C for 3 h, and the pre-frozen gel was freeze-dried to obtain a white fibrous solid;
[0048] 3) The white fibrous solid obtained in step 2) was placed in a corundum boat and placed in the middle of a tube furnace, calcined at 450°C for 2 h under N2 atmosphere, and cooled to room temperature to obtain a porous boron nitride precursor;
[0049] 4) The porous boron nitride precursor obtained in step 3) was placed in an acetone solution and stirred, 0.112 g of Pd(OAc)2 was added at 0°C and the reaction was continued to stir for 3 h, the filter cake was obtained by suction filtration, and a light yellow solid was obtained by drying under an infrared lamp;
[0050] 5) The light yellow solid obtained in step 4) was placed in a corundum boat and placed in the middle of a tube furnace, calcined at 800°C for 2 h under N2 atmosphere, cooled to room temperature, and the obtained gray-black solid was washed with water and alcohol, dried under an infrared lamp, and a single palladium atom modified porous boron nitride nanomaterial was obtained after drying, denoted as Pd-BNPs-800.
[0051] Example 4:
[0052] 1) 1.575 g of melamine and 1.545 g of boric acid were weighed and mixed uniformly, and then 100 ml of deionized water was added to prepare a sol-gel, a calcium hydroxide solution and an ammonia solution were slowly added to adjust the pH to 8-9, and a white gel was obtained under magnetic stirring at 40°C for 24 h;
[0053] 2) The gel obtained in step 1) is pre-frozen at -60 to -65°C for 3h, and the pre-frozen gel is freeze-dried to obtain a white fibrous solid;
[0054] 3) The white fibrous solid obtained in step 2) is placed in a corundum boat and placed in the middle of a tube furnace, calcined at 450°C for 2h under N2 atmosphere, cooled to room temperature to obtain a porous boron nitride precursor;
[0055] 4) The porous boron nitride precursor obtained in step 3) is placed in an acetone solution and stirred, 0.112g Pd(OAc)2 is added at 0°C and the reaction is continued to stir for 3h, the filter cake is obtained by suction filtration, and a light yellow solid is obtained by infrared lamp drying;
[0056] 5) The light yellow solid obtained in step 4) is placed in a corundum boat and placed in the middle of a tube furnace, calcined at 600°C for 2h under N2 atmosphere, cooled to room temperature, and the obtained gray-black solid is washed with water, alcohol, and dried by infrared lamp, and the single-palladium atom modified porous boron nitride nanomaterial is obtained after drying, which is recorded as Pd-BNPs-600.
[0057] The single-palladium atom modified porous boron nitride nanomaterials obtained in the above examples at different calcination temperatures have similar morphologies and can all be used for catalyzing Suzuki coupling reaction.
[0058] Comparative Example 1:
[0059] 1) 1.0g of BNPs-1100 material prepared in Example 1 is placed in a 100ml tomato-shaped bottle, 50ml of acetone is added, and ultrasonic is performed for 1h;
[0060] 2) The solution obtained in step 1) is stirred at room temperature, 0.112g Pd(OAc)2 is added and the stirring is continued for 24h, and the light yellow solid is obtained by suction filtration, acetone washing 3 times, and infrared lamp drying;
[0061] 3) The light yellow solid obtained in step 2) is poured into a 100ml tomato-shaped bottle, 50ml of deionized water is added, and after stirring uniformly, 85% of hydrazine hydrate is added dropwise until the light yellow solution becomes gray-black, and then stirring for 0.5h, the gray-black solid is obtained by suction filtration, ethanol washing 3 times, and infrared lamp drying;
[0062] 4) The gray-black solid obtained in step 3) is poured into a 100ml tomato-shaped bottle, 50ml of ethanol, acetonitrile, and toluene are added in sequence, each is refluxed for 2h, and the gray-black porous boron nitride supported palladium nanomaterial is obtained by suction filtration, ethanol washing 3 times, and infrared lamp drying, which is recorded as PdNPs / BN.
[0063] Application Example 1:
[0064] Pd-BNPs-1100 catalyzed Suzuki coupling reaction of 2-bromobenzonitrile and p-tolylboronic acid, the specific process and results as follows:
[0065] Under normal pressure air atmosphere, 50 mL of a flask was added to the palladium catalyst Pd-BNPs-1100 (10 mg, 0.0022 mmol-Pd), 2-bromobenzonitrile (1.0 mmol), p-tolylboronic acid (1.02 mmol), anhydrous potassium carbonate (2.0 mmol), anhydrous ethanol (4 mL), deionized water (4 mL), stirring at room temperature, 3 h after thin layer chromatography (TLC) test to prove that the reactants have been completely reacted; the recovered catalyst was filtered with filter paper, the separated material on the filter paper was washed with ethyl acetate, water and ethanol to obtain the catalyst, the separated catalyst was used for the next cycle of catalytic test; the filtrate was extracted with ethyl acetate and water; the ethyl acetate extract was washed with saturated brine and dried with anhydrous sodium sulfate, filtered; the ethyl acetate was evaporated by rotary evaporator to obtain white solid, then purified by silica gel column chromatography to obtain white solid product 2-cyano-4'-methyl biphenyl, yield 99%; the recovered catalyst after reaction was tested for cycle stability, under the same conditions, the reaction yield was 99%, 99%, 99%, 98%, 97%, 97%, respectively, as shown in Figure 5 The palladium monatomic catalyst has high catalytic activity and stability.
[0066] Comparative application example 1: Pd(OAc)2 catalyzed Suzuki coupling reaction of 2-bromobenzonitrile and p-tolylboronic acid, the specific process and results as follows:
[0067] Under normal pressure air atmosphere, 50 mL of a flask was added to the palladium catalyst Pd(OAc)2 (10 mg), 2-bromobenzonitrile (1.0 mmol), p-tolylboronic acid (1.02 mmol), anhydrous potassium carbonate (2.0 mmol), anhydrous ethanol (4 mL), deionized water (4 mL), stirring at room temperature, 3 h after thin layer chromatography (TLC) test to prove that the reactants have been completely reacted; after reaction, the product was extracted with ethyl acetate and water; the ethyl acetate extract was washed with saturated brine and dried with anhydrous sodium sulfate, filtered; the ethyl acetate was evaporated by rotary evaporator to obtain light yellow solid, then purified by silica gel column chromatography to obtain light yellow solid product 2-cyano-4'-methyl biphenyl, yield 99%; the product color was not correct after reaction, the product purity was not good, further purification work was needed, and Pd(OAc)2 was difficult to separate and recover after catalytic reaction, and could not be reused.
[0068] Comparative application example 2: PdNPs / BN catalyzed Suzuki coupling reaction of 2-bromobenzonitrile and p-tolylboronic acid, the specific process and results as follows:
[0069] In an air atmosphere at normal pressure, a 50 mL gourd-shaped bottle was added with a palladium catalyst PdNPs / BN (10 mg), 2-bromobenzonitrile (1.0 mmol), p-methylphenylboronic acid (1.02 mmol), anhydrous potassium carbonate (2.0 mmol), anhydrous ethanol (4 mL), deionized water (4 mL), and stirring at room temperature for 3 h, and then thin layer chromatography (TLC) was used to verify that the reactants had completely reacted; the catalyst was recovered by filtration, and the separated substance on the filter paper was washed with ethyl acetate, water and ethanol to obtain the catalyst, and the separated catalyst was used for the next cycle of catalytic test; the filtrate was extracted with ethyl acetate and water; the ethyl acetate extract was washed with saturated brine and dried with anhydrous sodium sulfate, and then filtered; the ethyl acetate was evaporated by a rotary evaporator to obtain white solid, and then column chromatography on silica gel was used for purification to obtain white solid product 2-cyano-4'-methylbiphenyl, with a yield of 97%; the catalyst after the reaction was recovered for stability test, and under the same conditions, the reaction yield was 95%, 91%, and it can be seen that the stability of PdNPs / BN is not high, and the palladium metal is easy to fall off from the boron nitride carrier during the catalytic reaction.
[0070] As can be seen by comparing application example 1 with comparative application example 1, the material Pd-BNPs-1100 of the present application maintains high catalytic activity of Pd(OAc)2 at a low palladium loading (palladium content: 2.33 wt%), and according to the color of the product, there is residual metal palladium in the product of the Pd(OAc)2 catalytic reaction, but the Pd-BNPs-1100 catalyst does not have this problem; as can be seen by comparing application example 1 with comparative application example 2, the Pd-BNPs-1100 has high stability.
[0071] The above examples are only preferred embodiments of the present application, and are not intended to limit the embodiments. The protection scope of the present application should be subject to the scope defined by the claims. Other different forms of changes or variations can be made on the basis of the above description. The changes or variations thus extended are still within the protection scope of the present application.
Claims
1. A method for preparing a single palladium atom modified porous boron nitride nanomaterial, characterized in that: 1) melamine and boric acid are mixed, and the pH of the system is adjusted to 8-9, and a sol-gel is prepared by stirring at 40-80 ℃ in a constant temperature water bath for 24 h; 2) the gel obtained in step 1) is pre-frozen at -60 to -65 ℃ for 3 h, and the pre-frozen gel is freeze-dried to obtain a white fibrous solid; 3) the white fibrous solid obtained in step 2) is calcined at 450-500 ℃ for 2-4 h under N2 atmosphere protection, and cooled to room temperature to obtain a porous boron nitride precursor; 4) the porous boron nitride precursor obtained in step 3) is placed in an acetone solution and stirred, and Pd(OAc)2 is added at 0 ℃ and the stirring reaction is continued for 3 h, then the filter cake is obtained by suction filtration, and a light yellow solid is obtained by infrared lamp drying; 5) the light yellow solid obtained in step 4) is calcined at 600-1100 ℃ for 2 h under N2 atmosphere protection, and cooled to room temperature, and the obtained gray-black solid is washed with water and alcohol, and dried by infrared lamp to obtain a single palladium atom modified porous boron nitride nanomaterial. The material is a single palladium atom modified porous boron nitride nanomaterial dried by an infrared lamp, with a particle size of 5-400 nm and a drying temperature of 70-100 ℃. The molar ratio of melamine to boric acid is 1:2-3; when the dosage of melamine is 10 mmol, the addition amount of Pd(OAc)2 is 0.5-2 mmol. The metal palladium with a particle size of 5-400 nm is dispersed on the surface and inside of the porous boron nitride nanomaterial in the form of a single atom prepared by the method of claim 1. The loading amount of the active metal palladium is 0.1-5% of the total mass of the material. The single palladium atom modified porous boron nitride nanomaterial is used as a catalyst for Suzuki coupling reaction.
2. The method of claim 1, wherein: The Suzuki coupling reaction is the reaction of organoboron compounds and organic halogen compounds at room temperature under the catalysis of the material of claim 4 as a catalyst, under normal pressure air atmosphere, with water and non-toxic organic solvents as reaction solvents; wherein, when the halide in the reaction substrate is 1 mmol, the addition amount of catalyst is 0.01-0.05 g.
3. The method of claim 1, wherein: 4. The monopalladium atom decorated porous boron nitride nanomaterial prepared by the method of claim 1, wherein: 5. The material of claim 4 wherein: 6. Use of the single palladium atom decorated porous boron nitride nanomaterial of claim 4, wherein: 7. Use according to claim 6, characterized in that:
Citation Information
Patent Citations
Preparation method of porous boron nitride nanofibers
CN104528671A
Catalyst for catalyzing Suzuki coupling reaction under normal temperature and normal pressure
CN109364921A
Nitride supported palladium catalyst and preparation method and application thereof
CN114100653A
Porous boron nitride and preparation method thereof, nanogold boron nitride composite photocatalyst and preparation method and application thereof
CN114751388A
Monatomic hydrogenation catalyst as well as preparation method and application thereof
CN116440936A